Exploring Attitude toward Virtual Bank Cards Using Nudge Theory and Experimental Analysis - Anysiadou, Melpomeni (Business and Economic Research, 2023)
<p class="ber-body" style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Purpose: The study aimed to investigate Greek consumers’ attitudes and actual behavior toward virtual bank cards and to show whether Experimental Economics can incentivize these banking products. <p class="ber-body" style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Methodology: For data collection, a specially designed experiment was conducted among Greek consumer samples according to Experimental Economics and Nudging Theory principles. Econometric analysis was conducted through Multi-level Models and Bivariate statistical tests. <p class="ber-body" style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results: Results suggest that demographic characteristics such as age combined with personalization and consumer risk perception play an important role in virtual bank card adoption. The youngest consumers are optimistic about their use, while the oldest are negative. Furthermore, Experimental Economics and Nudging Theory could identify behavioral changes. <p class="ber-body" style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Novelty: The study’s novelty and uniqueness are based on investigating Greek consumers’ attitudes and behavior towards new and innovative banking products, which still need to be well known. The research methodology is also a groundbreaking feature of the study, as Experimental Economics is the most appropriate method to study human behavior and its unconscious influencing factors that cannot be studied in other ways.